Predicting Domain-Specific Health-Related Quality of Life Using Acute Infarct Volume. Issue 7 (July 2017) - Lin, Chen; Lee, Jungwha; Chatterjee, Neil; Corado, Carlos; Carroll, Timothy; Naidech, Andrew; Prabhakaran, Shyam
Abstract : Background and Purpose—: Limited data exist on the relationship between acute infarct volume and health-related quality of life (HRQOL) measures after ischemic stroke. We evaluated whether acute infarct volume predicts domain-specific Neuro-Quality of Life scores at 3 months after stroke. Methods—: Between 2012 and 2014, we prospectively enrolled consecutive patients with ischemic stroke and calculated infarct volume. Outcome scores at 3 months included modified Rankin Scale and Neuro-Quality of Life T scores. We evaluated whether volume organized by quartiles predicted modified Rankin Scale and HRQOL scores at 3 months using logistic and linear regression as appropriate, adjusting for relevant covariates. We calculated variance accounted for ( R 2 ) overall and by volume for each domain of HRQOL. Results—: Among 490 patients (mean age 64.2±15.86 years; 51.2% male; 63.3% White) included for analysis, 58 (11.8%) were disabled (modified Rankin Scale score of >2) at 3 months. In unadjusted analysis, the highest volume quartile remained a significant predictor of 1 HRQOL domain, applied cognition–general concerns ( R 2 =0.06; P <0.001). Our fully adjusted prediction model explained 32% to 51% of the variance in HRQOL: upper extremity ( R 2 =0.32), lower extremity ( R 2 =0.51), executive function ( R 2 =0.45), and general concerns ( R 2 =0.34). Conclusions—: Acute infarct volume is a poor predictor of HRQOL domains after ischemic stroke, with the exception of the cognitive domain. Overall, clinical and imaging variables explained <50% of the variance in HRQOL outcomes at 3 months. Our data imply that a broad range of factors, some known and others undiscovered, may better predict poststroke HRQOL than what is currently available. Abstract : Supplemental Digital Content is available in the text.